Pengaruh Problem Based Learning Berbantu Geoboard terhadap Kemampuan Berpikir Kritis Anak Kelas IV SD - Suryani, Ade; Fuadah, Yayu Tsamrotul; jam, Jam; Rodin, Sahrodin (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Improving critical thinking skills is one of the main goals of 21st century education, especially at the elementary school level. This ability is important to help students analyze problems, find solutions, and make decisions logically. However, initial observations showed that fourth-grade students of SD Negeri 1 Jatimulyo still had difficulty in developing this ability, especially in mathematics subjects that require an understanding of abstract concepts. Therefore, innovation in learning models is needed to support the improvement of students' critical thinking skills. One approach that can be used is a problem-based learning model that involves teaching aids, such as a geoboard. A geoboard is a simple but effective teaching aid that can help students understand geometric concepts through exploration and visualization activities. The use of this tool is expected to not only increase students' interest in learning but also hone their critical thinking skills in an interactive and fun way. This study was conducted to examine the effectiveness of this approach in improving students' critical thinking skills.